Analisis Kepuasan Nasabah Terhadap Pelayanan Bank Syariah Indonesia (BSI) - Henny Saraswati; Budi Sudrajat; Wahyu Hidayat; Triana Marsanda Herin; Desmiranti Rahma; Ari Ari (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Service is not just providing services to customers, but also understanding the needs and desires of customers. A good service must start from understanding the needs and desires of customers, providing the right solutions, always updating and improving services, listening to customer feedback, and always balanced with competitive prices and satisfying product quality. The purpose of this research is to analyze customer satisfaction on the quality of service provided by Bank Syariah Indonesia. This study uses quantitative research by collecting primary and secondary data from questionnaires. Customer satisfaction is the main key in maintaining the continuity of the banking business, so it is important for banks to always pay attention to customer needs and provide the best service. Therefore, it is necessary to analyze customer satisfaction with the services of Bank Syariah Indonesia.